(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2025)
In recent years the STEM (Science, Technology, Engineering, Arts and Mathematics) approaches have been disseminated throughout the world, and have also reached Brazil, where they are disseminated at events, published in periodicals and on educational websites, articles, dissertations and theses. The objective of this study was to analyze STEM considering the premises established by the STS Movement and Historical-Critical Pedagogy. The research was based on qualitative approaches and data collection was carried out through a survey of articles, dissertations, theses, books and book chapters. To analyze the data, we adopted the analytical cycle proposed by Robert Yin. In the results, we present characteristics that demarcate STEM and identify differences in relation to STS Education. We argue that one of the main differences between these currents is the critical perspective assumed by STS Education, at least in the Latin American context, corresponding to a curricular proposal that envisions the full exercise of citizenship, mainly with regard to social participation and interests linked to social transformation, contrasted with the pragmatic, economistic and market-oriented perspective typical of STEM projects, signaling an education that directs students primarily towards their professional choices, in the sense of meeting the specific demands established by the economy and the labor market.